FACTORS INFLUENCING TOURISTS PREFERENCES TO VISIT MT. PARAWAGAN IN RODRIGUEZ RIZAL: AN ASSESSMENT (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study investigates the key factors that influence tourists' decisions to visit Mt. Parawagan, a popular natural attraction. Using a comprehensive assessment approach, the research examines various elements such as environmental factors, cultural appeal, and infrastructure development that contribute to tourists' choices. By exploring these factors, the study seeks to provide insights on how these influences impact the attraction's appeal, offering recommendations to enhance its attractiveness and improve the overall tourist experience. The study involved 50 tourists selected to participate in the research. Data was collected using a survey questionnaire, which guided the investigation through a series of structured questions. The collected data was then analyzed using percentages and weighted means. The findings indicated that the majority of respondents strongly agreed that four key factors significantly influenced their decision to visit Mt. Parawagan. The study utilized surveys, interviews, and observational methods to examine how various factors influence tourists' preferences and behaviors toward Mt. Parawagan. The findings emphasize the importance of maintaining the mountain's natural beauty while simultaneously enhancing the overall tourist experience. This research offers valuable insights for the tourism sector, providing guidance to policymakers, local communities, and businesses in developing sustainable strategies that both promote tourism and protect the natural environment. The study examines the impact of tourism on the local community, highlighting socioeconomic benefits, environmental conservation, and the potential challenges faced. By understanding the factors that motivate tourists to visit Mt. Parawagan, the findings provide crucial insights for stakeholders in tourism, promoting effective conservation efforts and encouraging sustainable development practices in the region.
Keywords: tourism; mt. parawagan; tourist preferences; environmental conservation; socioeconomic benefits; sustainable tourism; local community; infrastructure development; natural attractions; cultural appeal